Technologies in biathlon: The role of equipment and innovations in performance enhancement - Alferova, A. (Emerging Joint and Sports Sciences, 2024)
Biathlon is the sport which involves cross-country skiing and rifle shooting and therefore requires stamina, agility and shooting Range. Over the years amazing technological improvements have proven to be a central key to this complicated game in terms of performance. This paper aims to address a historical view on the development of the biathlon equipment, whose main components are skis, rifles, costumes, and information technologies to support athletes. Technological advancements such as lightweight or durable materials, ergonomic design of rifle and genuine time performance identification techniques have transformed training methods and competitive techniques. Issues of the ethical andthe financial aspect are also raised in the given discussion, with regard to the differences in the availability of the new technologies as well as their potential to affect the gear's inclusiveness to the sport. Down the line, novelage potentialities such as AI, VR, and sustainable fabrics còn hinted at the opportunity for a continued disruption of biathlon. What has been highlighted from this analysis, is the main challenge of adopting modern technology and innovation in organizing sports while avoiding a shift in the masses' sporting events, especially to the benefit of a classification of athletes.